Managing External Relations in Schools and Colleges : International Dimensions. - Lumby, Jacky (Centre for Educational Leadership and Management., 1999)
In the last 20 years, series of government-led initiatives world-wide have led to the marketization of education. Managing external relations has become an important role for leaders of schools and colleges, as self-management requires them to think strategically and act responsively. Scanning and responding to the external environment lies at the heart of ensuring quality educational provision, and surviving as a credible learning organization. This book examines the key issues for educational institutions in managing the range of external relations. The editors believe that.